Paternal Exposure to Environmental Chemical Stress Affects Male Offspring's Hepatic Mitochondria. (14th November 2017) - Godschalk, Roger; Remels, Alex; Hoogendoorn, Camiel; van Benthem, Jan; Luijten, Mirjam; Duale, Nur; Brunborg, Gunnar; Olsen, Ann-Karin; Bouwman, Freek G; Munnia, Armelle; Peluso, Marco; Mariman, Edwin; et al.
Abstract: Preconceptional paternal exposures may affect offspring's health, which cannot be explained by mutations in germ cells, but by persistent changes in the regulation of gene expression. Therefore, we investigated whether pre-conceptional paternal exposure to benzo[a]pyrene (B[a]P) could alter the offspring's phenotype. Male C57BL/6 mice were exposed to B[a]P by gavage for 6 weeks, 3× per week, and were crossed with unexposed BALB-c females 6 weeks after the final exposure. The offspring was kept under normal feeding conditions and was sacrificed at 3 weeks of age. Analysis of the liver proteome by 2D-gel electrophoresis and mass spectrometry indicated that proteins involved in mitochondrial function were significantly downregulated in the offspring of exposed fathers. This down-regulation of mitochondrial proteins was paralleled by a reduction in mitochondrial DNA copy number and reduced activity of citrate synthase and β-hydroxyacyl-CoA dehydrogenase, but in male offspring only. Surprisingly, analysis of hepatic mRNA expression revealed a male-specific up-regulation of the genes, whose proteins were downregulated, including Aldh2 and Ogg1 . This discrepancy could be related to several selected microRNA (miRNA)'s that regulate the translation of these proteins; miRNA-122, miRNA-129-2-5p, and miRNA-1941 were upregulated in a gender-specific manner. Since mitochondria are thought to be a source of intracellular reactive oxygen species, we additionally assessed oxidatively-induced DNA damage. Both 8-hydroxy-deoxyguanosine and malondialdehyde-dG adduct levels were significantly reduced in male offspring of exposed fathers. In conclusion, we show that paternal exposure to B[a]P can regulate mitochondrial metabolism in offspring, which may have profound implications for our understanding of health and disease risk inherited from fathers.